Age‐related changes in the fractal dimension of the retinal microvasculature, effects of cardiovascular risk factors and smoking behaviour. Issue 5 (7th November 2021) - Lemmens, Sophie; Luyts, Martial; Gerrits, Nele; Ivanova, Anna; Landtmeeters, Charlien; Peeters, Reinout; Simons, Anne‐Sophie; Vercauteren, Julie; Sunaric‐Mégevand, Gordana; Van Keer, Karel; Molenberghs, Geert; De Boever, Patrick; et al.
Abstract: Purpose: This cross‐sectional study investigates the association between retinal vessel complexity and age and studies the effects of cardiovascular health determinants. Methods: Retinal vessel complexity was assessed by calculating the box‐counting fractal dimension (Df ) from digital fundus photographs of 850 subjects (3–97 years). All photographs were labelled as 'non‐pathological' by the treating ophthalmologist. Results: Statistical models showed a significantly decreasing relationship between age and Df (linear: R ‐squared = 0.1897, p < 0.0001; quadratic: R ‐squared = 0.2343, p < 0.0001; cubic: R ‐squared = 0.2721, p < 0.0001), with the cubic regression model offering the best compromise between accuracy and model simplicity. Multivariate cubic regression showed that age, spherical equivalent and smoking behaviour have an effect (p < 0.0001) on Df . A significantly increasing effect of the number of pack‐years on Df was observed (effect: 0.0004, p = 0.0017), as well as a significantly decreasing effect of years since tobacco abstinence (effect: −0.0149, p < 0.0001). Conclusion: We propose using a cubic trend with age, refractive error and smoking behaviour when interpreting retinal vessel complexity.